Improving Children's Literacy Through Wayang Media at Assalam Martapura Kindergarten - Noor Habibah; Uswatun Nisa; Herman Taufik; Noor Baiti (EDUJAVARE: International Journal of Educational Research, 2025)
Early childhood literacy development is a crucial foundation for children’s future academic achievement and communication skills, yet literacy learning in many early childhood institutions remains conventional and less engaging for young learners. This study aimed to improve children’s literacy skills through the use of wayang media at TK Assalam Martapura. The research employed a collaborative Classroom Action Research (CAR) design conducted in two cycles involving 15 children in Group A. Data were collected through observation, documentation, and assessment of teacher activities, student participation, and literacy outcomes covering listening, speaking, letter recognition, and early writing skills. The findings revealed significant improvement in children’s literacy development after the implementation of wayang-based learning activities. In the pre-intervention stage, 66.7% of children were categorized as “Not Yet Developed,” while by the end of Cycle II, 66.7% reached the “Very Well Developed” category and 33.3% achieved “Developing as Expected,” resulting in 100% classical completeness. The study concludes that wayang media effectively enhances children’s literacy skills by creating interactive, culturally relevant, and enjoyable learning experiences. This research contributes to the development of innovative early childhood literacy instruction by integrating local cultural heritage into meaningful educational practices that support children’s language, creativity, and active participation.